PENGARUH SUBSTITUSI UBI JALAR UNGU (Ipomoea batatas) SERTA PERBANDINGAN KACANG KORO (Canavalia ensiformis) DENGAN SUSU SKIM TERHADAP KARAKTERISTIK ES KRIM - Tantan Widiantara (Pasundan Food Technology Journal (PFTJ), 2019)
This research was aimed to determine and to assess the influence of the substitution of purple sweet potato and the comparison between skim milk and jack bean extract to the characteristic of purple sweet potato ice cream. The benefits of this research are to diversifying local food-based products, to increase the value of jack bean and purple sweet potato, and as the reference for the researchers about the process of making purple sweet potato ice cream. This research consist of two stages. The first stage is preliminary research, then followed by the second stage; main research. The experiment was designed using Randomized Block Design (RBD) with (3x3) factorial pattern which is consist of 2 (two) factors. The first factor is the substitution of purple sweet potato (17,5% ; 22,5% ; 27,5%) and the second factor is the comparison between skim milk and jack bean extract (80%:20% ; 70%:30% ; 60%:40%), each combination was replicated three times. The results of the preliminary stages showed that jack bean extract contains HCN levels of 0.04968 mg/kg and protein content of 2.0499%, antioxidant activity of purple sweet potato paste of 178.218 ppm. The results of the main research showed that the substitution of purple sweet potato had an affect on protein content, fat content, overrun, attributes of color, aroma, taste, and texture of the ice cream. The comparison of skim milk and jack bean extract affect the protein content, attributes of color, aroma, taste, and texture of ice cream. The interaction between the two effects on protein content, fat content, attributes of color, taste, and texture of purple sweet potato ice cream. The antioxidant activity of the highest protein sample was 791.403 ppm.